IMPLEMENTASI UML PADA PERANCANGAN SISTEM INFORMASI PELATIHAN KERJA DI BALAI LATIHAN KERJA KOTA MOJOKERTO - Susanto, Dimas Dwi; Cahyono, Dwi (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
This study examines how to use the Unified Modeling Language (UML) to create a job training information system at the Mojokerto City Job Training Center. This system will replace the training management and registration process that is still done manually. Diagrams such as use cases, classes, sequences, and activities are used in UML to model the structure and flow of the system in design. The waterfall model is also used in software development and includes the steps of planning, needs analysis, design, implementation, testing, and maintenance. The implementation of the system results in a web-based application that facilitates the enrollment process. In addition, UML diagrams have been shown to be a useful tool for modeling systems that are structured and easily understood by users. More than 85% of the participants tested found the UML diagram visualization helpful. This information system facilitates the management of training data and makes the training process easier for participants and managers. To improve the user experience, a more in-depth study of the user interface (UI) and the use of system development techniques other than waterfall are suggestions for future research.